The role of libraries in supporting agricultural policy research: Evidence from selected university and research institute libraries in Nigeria - Rhoe, Valerie; Oboh, Victor; Shelton, Peter (International Food Policy Research Institute, 2010)
Agriculture is the largest contributor to the economic well-being of most Nigerians. For the agriculture sector to continue to grow, research-based knowledge of the existing agricultural practices, the potential of the sector, the approach for transforming the sector, and the impact of the transformation on the economy, sector, and population is needed. It has also been shown that agriculture R&D could increase agriculture growth and reduce poverty (Fan 2008; Thirtle et al. 2003). Therefore, research-based evidence is important to guide decisions that affect Nigeria's agriculture sector and its people. The quality and effectiveness of policy-making depend to a large extent on the quality of knowledge on which decisions are based (Hovland, 2003). Policy decisions could be shaped by the political, institutional, and cultural environments in which information and knowledge are produced, disseminated, and exchanged among stakeholders. According to Carden (2004), research findings may not have immediate and direct influence on decisions, but over time, their impact can be seen more clearly. The release of a research report represents an occasion for collective discussion and perhaps reconsideration of the issues raised by the report. Thus, understanding how knowledge and information are produced and disseminated, and how policymakers use it, should be an essential piece of agriculture policy and development strategy. An effective national agricultural research system (NARS1) is required for high quality research. The NARS researchers need to have access to recent, high quality literature, methodology, and data; and the capacity to use this information analytically to lay a solid foundation for research applicable to Nigeria's agriculture sector. In addition, other stakeholders in the agriculture industry, such as policymakers, educators, students, development partners, members of the private sector, and extension personnel, need high quality, relevant, and timely agricultural information to make good strategic decisions (Popoola, 2008).